2021
DOI: 10.1007/s11606-020-06441-6
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Survey of Educational Resource Utilization and Perception Among Internal Medicine Residents

Abstract: BACKGROUND: New virtual resources ("novel resources") have been incorporated into medical education. No recent large studies about their use and perception among internal medicine (IM) residents exist. OBJECTIVE: Characterize the use and perceived helpfulness of educational resources. DESIGN: Nationwide survey from December 2019 to March 2020. PARTICIPANTS: IM residents in the USA. MAIN MEASURES: Residents were surveyed on their use and their perceived helpfulness of resources for both attaining general medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Our study shows a high rate of listenership among surveyed health care providers (101/125, 81%), which is consistent with numbers from other recent studies showing podcast listenership rates among internal medicine and emergency medicine residents of 59% and 89%, respectively [ 18 , 19 ]. Medical podcasts represent an accessible and flexible means of continuing medical education (CME) for health care professionals who have completed formal training, as well as for trainees who seek supplementation to more traditional avenues of medical education.…”
Section: Discussionsupporting
confidence: 92%
“…Our study shows a high rate of listenership among surveyed health care providers (101/125, 81%), which is consistent with numbers from other recent studies showing podcast listenership rates among internal medicine and emergency medicine residents of 59% and 89%, respectively [ 18 , 19 ]. Medical podcasts represent an accessible and flexible means of continuing medical education (CME) for health care professionals who have completed formal training, as well as for trainees who seek supplementation to more traditional avenues of medical education.…”
Section: Discussionsupporting
confidence: 92%
“…11 Podcasts are frequently used in place of textbooks and are often rated as being more helpful. 31 However, there are very few orthopaedic podcasts that are oriented to the education of trainees, with most of them intended instead for patient education. 32 In 2021, Raja et al found that, of 492 identified online websites with only orthopaedic content, only 16 (3.3%) were directed for orthopaedic learning and not patient education.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Podcasts are frequently used in place of textbooks and are often rated as being more helpful. 31 However, there are very few orthopaedic podcasts that are oriented to the education of trainees, with most of them intended instead for patient education. 32 In 2021, Raja et al.…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has seen an explosion in digital education resources such as podcasts, videos, blogs, and teaching via social media platforms such as Twitter and Instagram. 2 The popularization of free and open access medical education has revolutionized our ability to learn through several interactive formats featuring rapidly updated information, allowing users to keep up with the pace of scientific discovery. Access to expert opinion is now readily available through multiple modalities.…”
Section: Consumementioning
confidence: 99%